From Sidelines to Center Stage: Strategic HRM and Strategy Agility in Indonesian Football Clubs - Agustriyana, Darwis; Indra Taruna Anggapraja (Cita konsultindo, 2025)
This study explores how well Strategic Human Resource Management (SHRM) and Strategy Agility are applied in the top five Indonesian professional football clubs over the last three seasons. Although Indonesian football is growing, many clubs still face problems in managing people and adapting to changes. The research uses a descriptive method with questionnaire data to measure three aspects of SHRM (Coherence, Integration, Devolvement) and three aspects of Strategy Agility (Strategic Sensitivity, Collective Commitment, Resource Fluidity). The results show that clubs are generally strong in aligning HR practices with long-term goals and in responding to changes, but they still struggle with flexible resource use and leadership coordination. A strong positive link between SHRM and Strategy Agility was found, showing that better HR systems help clubs adapt more quickly. The study suggests giving more authority to managers, improving how clubs monitor changes, encouraging teamwork among leaders, and sharing good practices to improve management across clubs.